2019
DOI: 10.3906/bot-1905-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of boron toxicity responses via glutathione-dependent detoxification pathways at biochemical and molecular levels in Arabidopsisthaliana

Abstract: The fine-tuned regulation of the Halliwell-Asada cycle (ascorbate-glutathione pathway) in Arabidopsis thaliana under boron (B) toxicity was shown in our previous report. In this study, we investigated the expression levels of some members of the glutathione S-transferase (GST) superfamily, such as phi (GSTF2, GSTF6, GSTF7, and GSTF8), tau (GSTU19), and zeta (GSTZ1) classes in Arabidopsis thaliana that were exposed to 1 mM boric acid (1B) and 3 mM boric acid (3B). Additionally, the expression levels of genes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Studies have found that high concentrations of boric acid can induce antioxidant stress response in plants [55]. The expression levels of ATGSTU19 and ATGSTZ1 genes in A. thaliana were significantly increased under the stress of high concentration of boric acid [56]. There have been several reports demonstrating that the phytotoxicity of thiocyanates is caused by redox imbalance [57].…”
Section: Enhanced Thiocyanate Tolerance In Transgenic a Thalianamentioning
confidence: 99%
“…Studies have found that high concentrations of boric acid can induce antioxidant stress response in plants [55]. The expression levels of ATGSTU19 and ATGSTZ1 genes in A. thaliana were significantly increased under the stress of high concentration of boric acid [56]. There have been several reports demonstrating that the phytotoxicity of thiocyanates is caused by redox imbalance [57].…”
Section: Enhanced Thiocyanate Tolerance In Transgenic a Thalianamentioning
confidence: 99%